Binary Chiral Nanoparticles Exhibit Amplified Optical Activity and Enhanced Refractive Index Sensitivity. Issue 6 (21st January 2020) - Yang, Lin; Nandi, Proloy; Ma, Yicong; Liu, Junjun; Mirsaidov, Utkur; Huang, Zhifeng
Abstract: Metallic chiral nanoparticles (CNPs) with a nominal helical pitch ( P ) of sub‐10 nm contain inherent chirality and are promisingly applied to diverse prominent enantiomer‐related applications. However, the sub‐wavelength P physically results in weak optical activity (OA) to prohibit the development of these applications. Herein, a facile method to amplify the CNPs' OA by alloying the host CNPs with metals through a three‐step layer‐by‐layer glancing angle deposition (GLAD) method is devised. Promoted by the GLAD‐induced heating effect, the solute metallic atoms diffuse into the host CNPs to create binary alloy CNPs. Chiral alloying not only induces the plasmonic OA of the diffused solute and the created alloys but also amplifies that of the host CNPs, generally occurring for alloying Ag CNPs with diverse metals (including Cu, Au, Al, and Fe) and alloying Cu CNPs with Ag. Furthermore, the chiral alloying leads to an enhancement of refractive index sensitivity of the CNPs. The alloy CNPs with amplified plasmonic OA pave the way for potentially developing important chirality‐related applications in the fields of heterogeneous asymmetric catalysis, enantiodifferentiation, enantioseparation, biosensing, and bioimaging. Abstract : The host chiral nanoparticles (CNPs) are alloyed with metals, induced by physical vapor deposition‐caused heating effect, to generate binary CNPs. The alloying not only induces the plasmonic optical activity (OA) of the dopant metals and the created alloys, but also causes the host to amplify in the plasmonic OA and enhances the refractive index sensitivity.